Assessment of the ability of the triglyceride to high density lipoprotein cholesterol ratio to discrininate insulate resistance among Caribbean-born black persons with and without Hispanic ethnicity - Tull, E.S. (2013)
Aims to determine if the triglyceride (TG) to high density insulin lipoprotein (HDL) cholesterol (TG/HDL) ratio has similar utility for discriminating insulin resistance in Caribbean-born black persons with and without Hispanic ancestry.